2022
DOI: 10.1155/2022/4524637
|View full text |Cite
|
Sign up to set email alerts
|

Serum Endocan Levels and Subclinical Atherosclerosis in Patients with Chronic Kidney and End-Stage Renal Diseases

Abstract: Background and Aim. Chronic kidney disease (CKD) and its final stage: end-stage renal disease (ESRD), are common clinical conditions. Endocan is a human endothelial cell-specific molecule produced by endothelial cells. Its production is related to activation of endothelium and angiogenesis. In this study, we assessed the relation between serum endocan levels and subclinical atherosclerosis (SCA) in CKD and hemodialysis (HD) patients. Subjects and Methods. The present case control study enrolled 30 patients on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…An early cross-sectional study enrolling 251 patients with chronic kidney disease (CKD), stages 1–5, and 60 controls published almost a decade ago suggested that: (1) circulating endocan levels are significantly higher among subjects with CKD compared to the controls, (2) endocan levels are progressively higher across advanced stages of CKD, and (3) the circulating endocan levels among subjects with CKD are significantly correlated with inflammatory markers and indices of endothelial dysfunction, suggesting that it might be an important predictor of all-cause death among this specific population [ 17 ]. Similar results were obtained from another, recently published observational study which enrolled 30 patients with CKD stage 5 under hemodialysis, 30 patients with CKD not receiving hemodialysis, and 30 controls, which confirmed a strong relationship between endocan levels and the stage of CKD [ 69 ]. The interconnection between endocan levels, systemic inflammation, subclinical atherosclerosis, and endothelial dysfunction was also confirmed [ 69 ].…”
Section: Endocan and Renal Diseasesupporting
confidence: 85%
See 1 more Smart Citation
“…An early cross-sectional study enrolling 251 patients with chronic kidney disease (CKD), stages 1–5, and 60 controls published almost a decade ago suggested that: (1) circulating endocan levels are significantly higher among subjects with CKD compared to the controls, (2) endocan levels are progressively higher across advanced stages of CKD, and (3) the circulating endocan levels among subjects with CKD are significantly correlated with inflammatory markers and indices of endothelial dysfunction, suggesting that it might be an important predictor of all-cause death among this specific population [ 17 ]. Similar results were obtained from another, recently published observational study which enrolled 30 patients with CKD stage 5 under hemodialysis, 30 patients with CKD not receiving hemodialysis, and 30 controls, which confirmed a strong relationship between endocan levels and the stage of CKD [ 69 ]. The interconnection between endocan levels, systemic inflammation, subclinical atherosclerosis, and endothelial dysfunction was also confirmed [ 69 ].…”
Section: Endocan and Renal Diseasesupporting
confidence: 85%
“…Similar results were obtained from another, recently published observational study which enrolled 30 patients with CKD stage 5 under hemodialysis, 30 patients with CKD not receiving hemodialysis, and 30 controls, which confirmed a strong relationship between endocan levels and the stage of CKD [ 69 ]. The interconnection between endocan levels, systemic inflammation, subclinical atherosclerosis, and endothelial dysfunction was also confirmed [ 69 ].…”
Section: Endocan and Renal Diseasesupporting
confidence: 85%
“…Overall, our meta-analysis included 696 CKD patients and 335 controls from eight studies [ 3 , 9 11 , 21 , 22 , 26 , 31 ]. The meta-analysis of these studies revealed significantly higher circulating Endocan levels in CKD patients (SMD 1.34, 95% CI 0.20 to 2.48, p-value<0.01, Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of endocan levels between CKD patients on regular hemodialysis (HD) and non-dialyzed CKD patients was done in two studies [ 22 , 31 ]. Samouilidou et al [ 31 ] evaluated serum endocan in CKD patients with or without HD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation